Penerapan Bank Energi Surya sebagai Sumber Energi Mandiri untuk Penerangan Masyarakat di Dusun Batu Ampar Desa Mulyorejo - Riofaldi Putra Aditama; Dimas Dwi Febrian; Lila Ratna Indah Lestari; Silfiatul Mukaromah; Rijal Daivu Duri; Risse Entikaria Rachmanita (Indonesian Journal Publisher, 2023)
Solar Energy Bank is an activity of the Community Service Student Creativity Program (PKM-PM) in collaboration with Ayo Berbagi (ABG) partners and given to 24 houses of Dusun Batu Ampar RT 04/RW 17 which still do not have access to the PLN electricity network so that lighting conditions at night are very poor. The purpose of this program is to implement the Solar Energy Bank as an alternative source of electrical energy for night lighting with emergency lights and Internet of Things (IoT) based monitoring systems. The program implementation method uses 3 implementation techniques, extension techniques through socialization, then science and technology assistance techniques include preparation and implementation activities, and the third is training and mentoring techniques. Benchmarks for the success of community services activities are measured by questionnaires given to society before and after implementation of the solar energy bank. Based on the result of the questionnaire, the implementation of the Solar Energy Bank has helped solve lighting problems, provided community service satisfaction and increased knowledge regarding the use of solar energy as an alternative energy source and skills in operating the Solar Energy Bank for the people of Dusun Batu Ampar RT 04/RW 17.